Writing with Cultural Insight: Elevating Analytical Exposition through Local Culture and Project-Based Learning - Garim, Idawati; Latief, Nurlaela; Amaliah, Suci; Garing, Jusmianti (International Journal of Language Education, 2023)
This study examines the effectiveness of integrating project-based learning (PjBL) with the Latemmamala cultural approach in enhancing the analytical exposition writing skills of grade XI students at SMA Negeri 3 Soppeng. Utilizing a quantitative research design, the study assessed improvements in students' writing abilities through pre-test and post-test evaluations, focusing on grammar, vocabulary, mechanics, fluency, and organization. Results indicated a notable increase in students' writing skills, with the mean score rising from 1425 to 2240. The standard deviation decreased from pre-test (4.811) to post-test (3.185), suggesting a more uniform improvement among students post-intervention. The paired samples t-test further substantiated the efficacy of the intervention (t(observational) = 7.14, p < 0.05), indicating a significant enhancement in writing skills attributable to the culturally infused PBL methodology. The study revealed that integrating PBL with a cultural perspective not only improved students' writing proficiency but also enhanced their motivation, creativity, and engagement with the learning process. It demonstrated that the Latemmamala cultural theme enriched the learning environment, fostering a closer bond between teacher and students through continuous monitoring and support during the project work. Significant improvements were observed in various facets of writing, reflecting the approach's comprehensive impact. By demonstrating the potential of culturally responsive teaching strategies, this study provides a valuable model for educators seeking to foster more inclusive, engaging, and effective learning environments. It underscores the importance of integrating cultural heritage within a PjBL framework to enhance language education, offering new insights into the potential of culturally enriched PBL. This research contributes to the growing body of literature on the benefits of cultural approaches in education and highlights the efficacy of integrating the Latemmamala cultural approach in improving students' academic skills and cultural understanding